PENGARUH TINGKAT SUKU BUNGA DAN PDRB TERHADAP DEPOSITO DI PROVINSI ACEH BERDASARKAN DATA TAHUN 2005-2010 - Mtg, Mukhlis; Irwanto, Agus (JURNAL KEBANGSAAN, 2012)
The development and the rate of domestic interest is influenced by many factors such as; inflation, the bank conditing and monetary authority. The development and the rate of interest is one of the important things for monetary indicator. In the other side, the development of interest have to reflect some foundamental factors. In Indonesia, the rate of interest have influenced some kinds of choice in saving and depositing. In Aceh province, the growth of deposit budget has increased in the last five years. But, it is different with PDRB. Based on the constans price in 2005, it is around Rp. 36.287,92 million, while in 2010, it is only around Rp. 33.070 million. The result of this research, based on the secondary data, PDRB, and the rate of interest for 12 months, it will have the significant influence toward depositing to the environment conventional bank in Aceh province.